Nutrient Requirements of Beef Cattle: Eighth Revised Edition - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Since 1944, the National Research Council (NRC) has published seven editions of the Nutrient Requirements of Beef Cattle. This reference has guided nutritionists and other professionals in academia and the cattle and feed industries in developing and implementing nutritional and feeding programs for beef cattle. The cattle industry has undergone considerable changes since the seventh revised edition was published in 2000 and some of the requirements and recommendations set forth at that time are no longer relevant or appropriate. The eighth revised edition of the Nutrient Requirements of Beef Cattle builds on the previous editions. A great deal of new research has been published during the past 14 years and there is a large amount of new information for many nutrients. In addition to a thorough and current evaluation of the literature on the energy and nutrient requirements of beef in all stages of life, this volume includes new information about phosphorus and sulfur contents; a review of nutritional and feeding strategies to minimize nutrient losses in manure and reduce greenhouse gas production; a discussion of the effect of feeding on the nutritional quality and food safety of beef; new information about nutrient metabolism and utilization; new information on feed additives that alter rumen metabolism and postabsorptive metabolism; and future areas of needed research. The tables of feed ingredient composition are significantly updated. Nutrient Requirements of Beef Cattle represents a comprehensive review of the most recent information available on beef cattle nutrition and ingredient composition that will allow efficient, profitable, and environmentally conscious beef production.
Keywords: Agriculture

Nutrient Requirements of Fish and Shrimp - National Research Council (The National Academies Press, 2011)
Aquaculture now supplies half of the seafood and fisheries products consumed worldwide and is gaining international significance as a source of food and income. Future demands for seafood and fisheries products can only be met by expanded aquaculture production. Such production will likely become more intensive and will depend increasingly on nutritious and efficient aquaculture feeds containing ingredients from sustainable sources.
Keywords: Agriculture

Safety of Dietary Supplements for Horses, Dogs, and Cats - National Research Council (The National Academies Press, 2009)
Growing numbers of pet owners are giving their pets dietary supplements in hopes of supporting their health. Many people presume that supplements are safer than drugs, but the reality is that there are very limited safety data on dietary supplements for pets. Many challenges stand in the way of determining whether animal dietary supplements are safe and at what dosage. Supplements considered safe in humans and other species are not always safe in horses, dogs, and cats. An improved adverse event reporting system is badly needed. Also, the absence of laws and regulations that specifically address animal dietary supplements causes considerable confusion to the industry and to the public. Clear and precise regulations are needed to allow only safe dietary supplements on the market. This book examines issues in determining safety of animal dietary supplements in general, and the safety of three animal dietary supplements; lutein, evening primrose oil, and garlic, in particular.
Keywords: Agriculture; Conflict and Security Issues

Nutrient Requirements of Nonhuman Primates: Second Revised Edition - National Research Council (The National Academies Press, 2003)
This new release presents the wealth of information gleaned about nonhuman primates nutrition since the previous edition was published in 1978. With expanded coverage of natural dietary habits, gastrointestinal anatomy and physiology, and the nutrient needs of species that have been difficult to maintain in captivity, it explores the impact on nutrition of physiological and life-stage considerations: infancy, weaning, immune function, obesity, aging, and more. The committee also discusses issues of environmental enrichment such as opportunities for foraging.
Keywords: Agriculture; Biology and Life Sciences

Nutrient Requirements of Dairy Cattle: Eighth Revised Edition - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Since 1944, the National Research Council (NRC) has published seven editions of the Nutrient Requirements of Dairy Cattle. This reference has guided nutritionists and other professionals in academia and the dairy and feed industries in developing and implementing nutritional and feeding programs for dairy cattle. The eighth revised edition of the Nutrient Requirements of Dairy Cattle builds on the previous editions. A great deal of new research has been published and there is a large amount of new information for many nutrients. This book represents a comprehensive review of the most recent information available on efficient, profitable, and environmentally conscious dairy cattle nutrition and ingredient composition.
Keywords: Agriculture

Nutrient Requirements of Small Ruminants: Sheep, Goats, Cervids, and New World Camelids - National Research Council (The National Academies Press, 2007)
Updating two previous National Research Council publications, Nutrient Requirements of Sheep, Sixth Revised Edition, 1985, and Nutrient Requirements of Goats, First Edition, 1981, this new book provides an evaluation of the scientific literature on the nutrient requirements of small ruminants in all stages of life. In addition, effects of the environment, feed additives, and metabolism modifiers on nutrient requirements are addressed. Proper formulation of diets for small ruminants depends on adequate knowledge of their nutrient requirements. These requirements depend on the breed and age of the animal and whether he or she is exercising, pregnant, or lactating. Nutrient Requirements of Small Ruminants brings together a summary of this latest data with new and expanded information on the composition of feeds commonly consumed by small ruminants, both domestic and wild. For the first time this authoritative reference work includes information on cervids and camelids. Primarily intended for animal nutritionists, veterinarians, and other scientists, some sections will be useful to individual sheep and goat owners and managers and to those responsible for the care and management of wildlife species. As both a practical and a technical reference book, this material is written to ensure that diets of small ruminants contain adequate amounts of nutrients and that intakes of certain nutrients are not so excessive that they inhibit performance or impair health.
Keywords: Agriculture

Nutrient Requirements of Dogs and Cats - National Research Council (The National Academies Press, 2006)
Updating recommendations last made by the National Research Council in the mid-1980s, this report provides nutrient recommendations based on physical activity and stage in life, major factors that influence nutrient needs. It looks at how nutrients are metabolized in the bodies of dogs and cats, indications of nutrient deficiency, and diseases related to poor nutrition. The report provides a valuable resource for industry professionals formulating diets, scientists setting research agendas, government officials developing regulations for pet food labeling, and as a university textbook for dog and cat nutrition. It can also guide pet owners feeding decisions for their pets with information on specific nutrient needs, characteristics of different types of pet foods, and factors to consider when feeding cats and dogs.
Keywords: Agriculture; Biology and Life Sciences

Nutrient Requirements of Swine: Eleventh Revised Edition - National Research Council (The National Academies Press, 2012)
Since 1944, the National Research Council has published 10 editions of the Nutrient Requirements of Swine. This reference has guided nutritionists and other professionals in academia and the swine and feed industries in developing and implementing nutritional and feeding programs for swine. The swine industry has undergone considerable changes since the tenth edition was published in 1998 and some of the requirements and recommendations set forth at that time are no longer relevant or appropriate. The eleventh revised edition of the Nutrient Requirements of Swine builds on the previous editions published by the National Research Council. A great deal of new research has been published during the last 15 years and there is a large amount of new information for many nutrients. In addition to a thorough and current evaluation of the literature on the energy and nutrient requirements of swine in all stages of life, this volume includes information about feed ingredients from the biofuels industry and other new ingredients, requirements for digestible phosphorus and concentrations of it in feed ingredients, a review of the effects of feed additives and feed processing, and strategies to increase nutrient retention and thus reduce fecal and urinary excretions that could contribute to environmental pollution. The tables of feed ingredient composition are significantly updated. Nutrient Requirements of Swine represents a comprehensive review of the most recent information available on swine nutrition and ingredient composition that will allow efficient, profitable, and environmentally conscious swine production.
Keywords: Agriculture

Nutrient Requirements of Dairy Cattle: Seventh Revised Edition, 2001 - National Research Council (The National Academies Press, 2001)
This widely used reference has been updated and revamped to reflect the changing face of the dairy industry. New features allow users to pinpoint nutrient requirements more accurately for individual animals. The committee also provides guidance on how nutrient analysis of feed ingredients, insights into nutrient utilization by the animal, and formulation of diets to reduce environmental impacts can be applied to productive management decisions.
Keywords: Agriculture; Food and Nutrition

Nutrient Requirements of Horses: Sixth Revised Edition - National Research Council (The National Academies Press, 2007)
Proper formulation of diets for horses depends on adequate knowledge of their nutrient requirements. These requirements depend on the breed and age of the horse and whether it is exercising, pregnant, or lactating.
Keywords: Agriculture

Nutrient Requirements of Beef Cattle: Seventh Revised Edition: Update 2000 - National Research Council (The National Academies Press, 2000)
As members of the public becomes more concious of the food they consume and its content, higher standards are expected in the preparation of such food. The updated seventh edition of Nutrient Requirements of Beef Cattle explores the impact of cattle's biological, production, and environmental diversities, as well as variations on nutrient utilization and requirements. More enhanced than previous editions, this edition expands on the descriptions of cattle and their nutritional requirements taking management and environmental conditions into consideration. The book clearly communicates the current state of beef cattle nutrient requirements and animal variation by visually presenting related data via computer-generated models. Nutrient Requirements of Beef Cattle expounds on the effects of beef cattle body condition on the state of compensatory growth, takes an in-depth look at the variations in cattle type, and documents the important effects of the environment and stress on food intake. This volume also uses new data on the development of a fetus during pregnancy to prescribe nutrient requirements of gestating cattle more precisely. By focusing on factors such as product quality and environmental awareness, Nutrient Requirements of Beef Cattle presents standards and advisements for acceptable nutrients in a complete and conventional manner that promotes a more practical understanding and application.
Keywords: Agriculture

Nutrient Requirements of Laboratory Animals,: Fourth Revised Edition, 1995 - National Research Council (The National Academies Press, 1995)
In the years since the third edition of this indispensable reference was published, a great deal has been learned about the nutritional requirements of common laboratory species: rat, mouse, guinea pig, hamster, gerbil, and vole. The Fourth Revised Edition presents the current expert understanding of the lipid, carbohydrate, protein, mineral, vitamin, and other nutritional needs of these animals. The extensive use of tables provides easy access to a wealth of comprehensive data and resource information. The volume also provides an expanded background discussion of general dietary considerations. In addition to a more user-friendly organization, new features in this edition include:
Keywords: Biology and Life Sciences; Agriculture

Nutrient Requirements of Rabbits,: Second Revised Edition, 1977 - National Research Council (The National Academies Press, 1977)
Keywords: Agriculture

Nutrient Requirements of Mink and Foxes,: Second Revised Edition, 1982 - National Research Council (The National Academies Press, 1982)
Keywords: Agriculture

Nutrient Requirements of Poultry: Ninth Revised Edition, 1994 - National Research Council (The National Academies Press, 1994)
This classic reference for poultry nutrition has been updated for the first time since 1984. The chapter on general considerations concerning individual nutrients and water has been greatly expanded and includes, for the first time, equations for predicting the energy value of individual feed ingredients from their proximate composition. This volume includes the latest information on the nutrient requirements of meat- and egg-type chickens, incorporating data on brown-egg strains, turkeys, geese, ducks, pheasants, Japanese quail, and Bobwhite quail. This publication also contains new appendix tables that document in detail the scientific information used to derive the nutrient requirements appearing in the summary tables for each species of bird.
Keywords: Agriculture